USM INTERNATIONAL STUDENTS CELEBRATE 1st ISAN 2015 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 17 November 2015 – Universiti Sains Malaysia (USM) International Office and Postgraduate Students Association (PSA) recently held a celebration of the 1 International Students Appreciation Night (ISAN) 2015.